CONGENITAL AND ACQUIRED HEART DEFECTS IN CHILDREN - Yoldasheva Mehriniso Ne'mat's Qizi (Western European Studies, 2024)
This article discusses congenital and acquired heart defects in children
Keywords: Heart; vascular system; muscle; myocardium